1996
DOI: 10.1103/physrevb.54.3610
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistivity of thin films of the electron-doped high-TcsuperconductorNd1.85

Abstract: We report measurements of the magnetoresistance of Nd 1.85 Ce 0.15 CuO 4Ϯ␦ epitaxial thin films with varying oxygen content in magnetic fields H applied parallel (Hʈc͒ and perpendicular (HЌc͒ to the tetragonal c axis. We have observed critical scaling of the electrical resistivity that is consistent with a vortex-glass transition for a film with an optimum superconducting transition temperature T c of Ϸ22 K and Hʈc . The values of the zero-temperature upper critical field H c 2 (0)ϭ80 kOe and the in-plane zero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…43 For the n-type cuprates the upper critical field was determined from the fluctuation conductivity f luc . 44,45 Again, these values were larger than B * . In Ref.…”
Section: B Experimental Resultsmentioning
confidence: 83%
“…43 For the n-type cuprates the upper critical field was determined from the fluctuation conductivity f luc . 44,45 Again, these values were larger than B * . In Ref.…”
Section: B Experimental Resultsmentioning
confidence: 83%
“…Actually, this regime was only noticed in some early works focusing on Nd 2−x Ce x CuO 4Ϯ␦ ͑NCCO͒ thin films. 4,5 Among the previous studies on the UA regime many experiments indicated that T c gradually increases to a saturated value with the oxygen removal, 7,8,25,26 and some recent works on PCCO thin films 8 and NCCO polycrystals 26 even suggested that the samples would be decomposed with further deoxygenated annealing. However, in this work, we demonstrate in the single crystals that this OA regime is really a bulk characteristic of electron-doped cuprates in which the sample is not decomposed while T c decreases with the oxygen removal.…”
Section: A Phase Diagram Of T C Evolutionmentioning
confidence: 97%
“…While for electron-doped copper oxides such as RE 2−x Ce x CuO 4Ϯ␦ ͑RE =Pr,Nd,Sm,La͒ ͑RCCO͒, there is a long-standing issue that, besides doping carriers, annealing in a low-oxygen environment is necessary to induce superconductivity, 1,2 though the amount of the oxygen removed is extremely small, ␦ ϳ 0.01-0.04 ͑no more than 1%͒. 2 This oxygen-reduction annealing treatment drives the material continuously from an AF Mott insulator to a superconductor with very low normal-state resistivity, [3][4][5][6][7][8] accompanied by a sign change in Hall coefficient. 4,6,8 It was also suggested that oxygen-reduction process induces superconductivity by suppressing long-range AF order which seems to compete with superconducting order.…”
Section: Introductionmentioning
confidence: 99%
“…The mag netoresistance was studied for Nd 2 -x Ce x CuO 4 + δ epi taxial films with different oxygen concentrations; the slope of the upper critical field for optimally doped and optimally annealed sample was estimated as dH c2 /dT = -3.5 ± 0.3 kOe/K [15].…”
Section: Introductionmentioning
confidence: 99%